Perancangan Aplikasi Tutorial Turnitin Untuk Melacak Plagiasi Menggunakan Metode Prototype - Haris Jamaludin; Sulartopo Sulartopo; Nuris Dwi Setiawan (Elkom: Jurnal Elektronika dan Komputer, 2024)
This study focuses on creating a Turnitin tutorial application to track plagiarism using the prototype method approach. The purpose of this application is to make it easier for users to understand and utilize Turnitin as a reliable plagiarism detection tool in academic writing. The prototype method was chosen because it allows for rapid iteration and improvement based on user feedback, which is very important to improve the quality of the application. The development stages include creating an initial prototype, testing functions, and collecting feedback for design refinement. This study aims for the application to be developed to provide clear guidance and effective solutions in identifying and preventing plagiarism, while deepening users' understanding of the use of Turnitin. Thus, this application is expected to strengthen academic integrity and support ethical writing practices through integrated plagiarism detection technology.